Decision Support: Time for Collaboration - Guardia, A.; Section Editor for the IMIA Yearbook Section on Decision Support (Yearbook of Medical Informatics, 2011)
To summarize current outstanding research in the field of decision support.A selection of excellent research articles published in 2010 in the field of computerized clinical decision support systems.This selection of articles shows that deci- sion support systems (DSS) are getting better integrated into the electronic health record systems (EHR) and into the clinician’s workflow. As a result, there is a better collaboration between physicians and DSS, which improves the care of patients.
Keywords: Decision support systems; collaboration; electronic health record; medical data; integration; ubiquitous